Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Let's solve the quadratic equation [tex]\(x^2 + 12x + 36 = 0\)[/tex].
To find the solutions to the quadratic equation, we can use the quadratic formula, which is given by:
[tex]\[ x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \][/tex]
For the given equation [tex]\(x^2 + 12x + 36 = 0\)[/tex], we can identify the coefficients [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] as follows:
- [tex]\(a = 1\)[/tex]
- [tex]\(b = 12\)[/tex]
- [tex]\(c = 36\)[/tex]
Now, let's compute the discriminant [tex]\(\Delta\)[/tex] of the quadratic equation:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \Delta = 12^2 - 4 \cdot 1 \cdot 36 = 144 - 144 = 0 \][/tex]
Since the discriminant [tex]\(\Delta\)[/tex] is 0, there is exactly one real solution to the equation, which is given by:
[tex]\[ x = \frac{{-b}}{2a} \][/tex]
Substituting the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
[tex]\[ x = \frac{{-12}}{2 \cdot 1} = \frac{{-12}}{2} = -6 \][/tex]
Therefore, the value of [tex]\(x\)[/tex] that solves the quadratic equation [tex]\(x^2 + 12x + 36 = 0\)[/tex] is:
[tex]\[ x = -6 \][/tex]
So, the correct answer to the given question is:
[tex]\[ x = -6 \][/tex]
To find the solutions to the quadratic equation, we can use the quadratic formula, which is given by:
[tex]\[ x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \][/tex]
For the given equation [tex]\(x^2 + 12x + 36 = 0\)[/tex], we can identify the coefficients [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] as follows:
- [tex]\(a = 1\)[/tex]
- [tex]\(b = 12\)[/tex]
- [tex]\(c = 36\)[/tex]
Now, let's compute the discriminant [tex]\(\Delta\)[/tex] of the quadratic equation:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \Delta = 12^2 - 4 \cdot 1 \cdot 36 = 144 - 144 = 0 \][/tex]
Since the discriminant [tex]\(\Delta\)[/tex] is 0, there is exactly one real solution to the equation, which is given by:
[tex]\[ x = \frac{{-b}}{2a} \][/tex]
Substituting the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
[tex]\[ x = \frac{{-12}}{2 \cdot 1} = \frac{{-12}}{2} = -6 \][/tex]
Therefore, the value of [tex]\(x\)[/tex] that solves the quadratic equation [tex]\(x^2 + 12x + 36 = 0\)[/tex] is:
[tex]\[ x = -6 \][/tex]
So, the correct answer to the given question is:
[tex]\[ x = -6 \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.